A new species of Coenodomus Walsingham, 1888 (Epipaschiinae, Pyralidae, Lepidoptera) from India - Ranjan, Rahul; Singh, Navneet; Kirti, Jagbir Singh (Zootaxa, 2023)
In the present manuscript, one new species, Coenodomus wangi Ranjan, Singh & Kirti, sp. nov., is described and diagnosed with its closely similar species, C. dudgeoni Hampson, 1896 and C. rotundinidus Hampson, 1891. An updated checklist of global Coenodomus species is provided.